Efficacy and safety of Cerebrolysin treatment in early recovery after acute ischemic stroke: a randomized, placebo-controlled, double-blinded, multicenter clinical trial - Gharagozli, K (J Med Life, 2017)
Background and Purpose: The aim of this study was to evaluate the efficacy, safety, and tolerability of cerebrolysin in the early recovery phase after acute ischemic stroke. Methods. This prospective, randomized, double-blinded, placebo-controlled, multicenter, parallel-group study enrolled a total of 100 patients within 18 h after the onset of stroke. The patients were treated with Cerebrolysin (30 mL over seven days followed by 10 mL until day 30) or placebo once daily over a period of four weeks. Efficacy was primarily assessed by the NIH Stroke Scale at day 30, and additional parameters included the modified Rankin Scale, the Clinical Global Impression, the Patient Global Satisfaction (PGS) and the Mini Mental State Examination (MMSE). Nonparametric statistical procedures employing the Wilcoxon-Mann-Whitney test were used for data analysis. Safety and tolerability were assessed by adverse events, vital signs, and laboratory parameters. Results.The estimated effect size on the change from baseline in the NIH Stroke Scale on day 30 indicated a medium to large superiority of cerebrolysin compared to placebo (Mann-Whitney [MW] 0.66; 95% confidence interval [CI] 0.55-0.78, P=0.005). Similar effect sizes were reported for the modified Ranking Scale (MW 0.65; 95% CI 0.54-0.76; P=0.010) and the Clinical Global Impression (MW 0.70; 95% CI 0.55-0.85; P=0.006). Effect sizes in the MMSE and PGS did not reach statistical significance. No significant group differences were seen in any of the safety parameters. Conclusions. Cerebrolysin was effective, safe, and well tolerated in the early recovery phase after acute ischemic stroke and significantly improved neurological and global function outcomes compared to placebo.